Hematoma Block: An Effective Alternative for Pain Management and Procedural Sedation. (April 2021) - House, David Thomas
Abstract : Management of traumatic extremity injuries in the emergency department is typically time consuming, often requiring multiple resources including pain control and procedural sedation. A hematoma block is a safe and effective alternative treatment of pain and may eliminate the need for procedural sedation. The hematoma block requires fewer emergency department resources and may decrease time and costs that are associated with procedural sedation and analgesia. This technique is easily performed by the emergency nurse practitioner, and complications are rare. This article presents the appropriate technique required to perform a hematoma block for pain control and fracture reduction in patients with closed traumatic injuries.